Penegakan Pelanggaran Hak Cipta di Era Revolusi Industri: Studi Putusan - Sofia, Sofia; Disemadi, Hari Sutra; Agustianto, Agustianto (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: Changes in the industrial revolution have increased the risk of copyright infringement of products, which can be detrimental to the creator. Therefore, better protection is needed to address this high risk.Purposes of the Research:  This research aims to analyze law enforcement related to copyright infringement in the era of the Industrial Revolution through case studies of judges' decisions.Methods of the Research: The research method used is the normative legal method by analyzing legislation and Court Decisions Number 505 K/Pdt.Sus-HKI/2021 and Number 1933 K/Pid.Sus/2021 through literature study, by applying descriptive legal interpretation techniques to reach the right conclusion.Results of the Research: The results showed that law enforcement against copyright infringement involves two main approaches, namely preventive and repressive. The preventive approach is carried out through regulations that provide legal certainty, such as the presence of the Copyright Act. Meanwhile, the repressive approach is realized through legal proceedings in court and out of court to take action against violations that occur. This study highlights several cases of copyright infringement in Indonesia and shows the importance of strong law enforcement to protect the rights of creators in the digital age.